O uso do GeoGebra na construção de figuras dinâmicas de lugares geométricos no espaço - Silva, Joelson Lima da (2018)
This study aimed to show through 3D object construction using GeoGebra software as a support to the learning process in the content of geometric places in space. We highlight the use of GeoGebra software and its main tools in the fat and spatial geometry through the construction and visualization of the concepts presented in scripts for creation of at gures and in 3D. To do so, we present the GeoGebra software interface for at and spatial geometry. We present the denition of locus and propositions related to the subject and choose five locoes theoretically described for the step-by-step construction of 3D figures so that they can represent such objects dynamically. Through all the construction carried out, it was possible to confirm that GeoGebra software can aid in the learning process by opening up possibilities for a more effective, dynamic and constructivist education.